1995
DOI: 10.1111/j.1460-9592.1995.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic prophylaxis does not prevent emesis following strabismus surgery in children

Abstract: One hundred and twenty-one children were studied in this prospective, randomized double-blind, placebo-controlled comparison of the effectiveness of anticholinergic prophylaxis for the prevention of emetic symptoms following strabismus surgery. The children were allocated to three groups, to receive placebo (n = 40), glycopyrrolate (n = 40) or atropine (n = 41). The incidence of intraoperative oculocardiac reflex (OCR) and of postoperative emetic symptoms for 24 h was recorded. The incidence of OCR was 55% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(29 citation statements)
references
References 18 publications
0
26
1
2
Order By: Relevance
“…Antihistamines, although widely used for migraine, are generally recommended for motion sickness as they act at the level of the vestibular apparatus 43,52. Anti-cholinergic agents such as atropine and hyoscine are relatively ineffective in the treatment or prevention of vomiting due to causes other than motion sickness 52–54. The mechanism of action is not clearly understood in some antiemetic medications such as dexamethasone and trimethobenzamide.…”
Section: The Pathophysiology Of Vomiting and The Mechanisms Of Antiemmentioning
confidence: 99%
“…Antihistamines, although widely used for migraine, are generally recommended for motion sickness as they act at the level of the vestibular apparatus 43,52. Anti-cholinergic agents such as atropine and hyoscine are relatively ineffective in the treatment or prevention of vomiting due to causes other than motion sickness 52–54. The mechanism of action is not clearly understood in some antiemetic medications such as dexamethasone and trimethobenzamide.…”
Section: The Pathophysiology Of Vomiting and The Mechanisms Of Antiemmentioning
confidence: 99%
“…2 Administering atropine or glycopyrrolate decreases the incidence of OCR; 2,5,23,25 however, systematic prophylactic anticholinergic administration remained controversial in the past because it was associated with ventricular arrhythmias. Also, in most of these reports, the patients were receiving halothane anesthesia, which also increased the incidence of arrhythmias.…”
Section: Prevention Of Ocrmentioning
confidence: 99%
“…It has also been suggested that prophylactic anticholinergics be used to reduce the rate of PONV by decreasing the incidence of OCR; however, this option has not been demonstrated in pediatric strabismus. 25 …”
Section: Prevention Of Ocrmentioning
confidence: 99%
See 2 more Smart Citations